(untitled) (Marketing Journal, 2026)
This article examined the theoretical and practical aspects of developing medical tourism within the regional economy based on a cluster approach. The study substantiated the feasibility of forming medical clusters as an effective tool for enhancing region al competitiveness, attracting investment, and ensuring sustainable socio -economic development. The current state of clusterization in the Republic of Uzbekistan was assessed, and key directions as well as specific features of medical and № 1 -SON YANVA R, 202 6-YIL 490 pharmaceutical cluster development were identified. Particular attention was given to evaluating their multiplicative effects on related sectors of the economy. The findings demonstrated the significant role of state support and institutional mechanisms in stimulating medical tourism and creating favorable conditions for its further development at the regional level.